Cultural interests in Serbia: a look into the future - Mrđa, Slobodan M (Napredak, 2023)
Cultural interests represent one of the important aspects of cultural participation. Previous research into this aspect of cultural participation shows that the most favourite activities of Serbian citizens in their free time are mostly related to the private sphere of life in the domain of socializing and recreation, while activities related to public or private cultural consumption are relatively little present in the structure of free time activities. Therefore, it could be stated that the development of cultural interests takes place very slowly, if one can speak of any consistent development at all. In addition, the comparative analysis shows trends that are so stable that no significant changes can be expected in the domain of cultural interests of Serbian citizens in the coming period. However, at the beginning and during the pandemic, there were significant changes in the part of cultural participation, cultural consumption, which shifted to an electronic form, where cultural institutions began to offer digital content on the Internet. Such digital transformation of the cultural offer through the creation of digital cultural products and the digitization of cultural contents could have a significant impact on the development of cultural interests. The digital transformation has provided opportunities for greater accessibility of cultural products to individuals who previously had barriers to participating in cultural life, be it lack interest, distance, costs or physical limitations, as they can now access cultural events via the Internet.
Keywords: cultural interests; cultural participation; free time; Pandemic COVID-19; digital cultural contents; digital transformation; cultural practices